2004
DOI: 10.2214/ajr.182.3.1820683
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Pelvic Congestion Syndrome Using Transabdominal and Transvaginal Sonography

Abstract: Sonographic findings of pelvic congestion syndrome were dilated left ovarian vein with reversed caudal flow, presence of varicocele, dilated arcuate veins crossing the uterine myometrium, polycystic changes of the ovary, and variable duplex waveform during the Valsalva's maneuver. Combined transabdominal and transvaginal sonography are potentially useful as a noninvasive screening tool for determining which patients with chronic pelvic pain may benefit from selective ovarian venography and transcatheter emboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
215
2
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(242 citation statements)
references
References 8 publications
6
215
2
14
Order By: Relevance
“…In our study, the mean age of PVC incidence in women was 35 years and it was found to be similar to that in the literature (7). In women, the youngest patient detected with PVC was aged 22 years and para 2.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the mean age of PVC incidence in women was 35 years and it was found to be similar to that in the literature (7). In women, the youngest patient detected with PVC was aged 22 years and para 2.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, venous varicosity does not always lead to chronic pelvic pain (7). While Park et al (7) found that the left ovarian vein diameter was >5 mm in 28 (90.3%) of 31 patients in case-control studies, they found it to be >5 mm in 16 (45%) patients in the control group of 35 patients. However, they detected varicosity only in four of these 16 healthy patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Suffice it to say that with modern ultrasound systems, direct assessment of the ovarian and internal iliac veins can be made very effectively in the vast majority of patients. Where suspicion of pelvic venous incompetence exists on clinical grounds or on the basis of the findings in the lower extremity veins, pelvic vein assessment incorporating transabdominal survey of the ovarian and internal iliac vein should be performed 22 , 23 .…”
Section: Pelvic and Ovarian Veinsmentioning
confidence: 99%
“…Pelvic US (transabdominal or transvaginal) is often the first-line examination (10,11). With CT, the tubular structure of dilated ovarian veins and the pattern of their enhancement after intravenous administration of contrast medium allow the investigator to distinguish them from adnexal masses or lymphadenopathy (12,13).…”
Section: Discussionmentioning
confidence: 99%